2021
DOI: 10.1016/j.thromres.2021.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Absence of hypercoagulability after nCoV-19 vaccination: An observational pilot study

Abstract: Background It is still unknown whether COVID-19 vaccines induce a prothrombotic state or increase the hypercoagulable condition in subjects with a predisposition to thrombosis. Objectives We evaluated the coagulation profile in a series of healthy subjects who received the first dose of the BNT162b2 or the ChAdOx1 vaccines and assessed whether hypercoagulability developed. Patients/methods Volunteers among the staff of the University of Padua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…A prospective Chinese cohort study suggested that inactivated COVID-19 vaccine (BBIBP-CorV, Sinopharm) did not influence the profile of antiphospholipid antibody and anti-PF4heparin antibody nor increased the risk of thrombosis (60). Additionally, Campello et al (61) suggested that significant activation of fibrinogen-driven coagulation, plasma thrombin generation, or clinically meaningful platelet aggregation did not occur after ChAdOx1 nCoV-19 or BNT162b2 vaccination. Nevertheless, Simpson et al(62) evaluated associations between ChAdOx1 nCoV-19 or BNT162b2 vaccination and hematological and vascular adverse events.…”
Section: Stroke Following Covid-19 Vaccinationmentioning
confidence: 99%
“…A prospective Chinese cohort study suggested that inactivated COVID-19 vaccine (BBIBP-CorV, Sinopharm) did not influence the profile of antiphospholipid antibody and anti-PF4heparin antibody nor increased the risk of thrombosis (60). Additionally, Campello et al (61) suggested that significant activation of fibrinogen-driven coagulation, plasma thrombin generation, or clinically meaningful platelet aggregation did not occur after ChAdOx1 nCoV-19 or BNT162b2 vaccination. Nevertheless, Simpson et al(62) evaluated associations between ChAdOx1 nCoV-19 or BNT162b2 vaccination and hematological and vascular adverse events.…”
Section: Stroke Following Covid-19 Vaccinationmentioning
confidence: 99%
“…Circulating platelets serve as a reservoir of immunomodulatory molecules [201]. However, no significant activation of fibrinogen-driven coagulation, plasma thrombin generation, or clinically meaningful platelet aggregation after AstraZeneca/Oxford or BNT162b2 vaccination was observed [209].…”
Section: Pathophysiological Hypothesesmentioning
confidence: 99%
“…Particularly, in case VST is associated with thrombocytopenia, the outcome can be fatal or unfavourable (Table 1 ). Though the pathophysiological mechanism underlying the development of thrombosis after SARS-CoV-2 vaccinations has not been fully elucidated, there are indications that the immune response towards the vaccine creates a state of hypercoagulability similar to hypercoagulability in SARS-CoV-2 infections [ 7 ], but hypocoagulability has been also reported [ 8 ]. This review aimed at summarising and discussing previous and recent advances regarding the diagnosis, pathogenesis, treatment, and outcome of post-SARS-CoV-2 vaccination venous sinus thrombosis.…”
Section: Main Textmentioning
confidence: 99%